ANALISIS KOMPARASI KARAKTER SOCIOPRENEUR RELAWAN GARDA PANGAN TERHADAP MOTIVASI MENDUKUNG PROGRAM KETAHANAN PANGAN - Nabilah, Dalilah; Yektiningsih, Endang; Setyadi, Taufik (Jurnal Hutan Tropis, 2025)
Food waste in Indonesia has become a serious issue that threatens food security, despite the country being classified as an upper middle-income country. In an effort to address this challenge, Garda Pangan, a Surabaya-based sociopreneur, has been active in minimizing food waste and food inequality in Surabaya. Through its programs, Garda Pangan involves sociopreneurs, namely volunteers, in distributing potentially wasted food to underprivileged communities. This study aims to analyze sociopreneur character and motivation and to describe the profile of Garda Pangan volunteers who can optimally support food security programs. Data for this study was collected through a structured questionnaire and processed using independen sample t-test to analyze the sociopreneur character and motivation of volunteers. The results show that Garda Pangan volunteers have a strong sociopreneur character, driven by empathy and social responsibility towards the issue of food waste and food inequality in Surabaya. Their involvement as volunteers is evidence of their commitment to food security. This research is expected to raise public awareness and encourage participation in supporting food security in Indonesia.